Students' attitudes towards their EFL lessons and teachers: - Žefran, Mojca (Revija za elementarno izobraževanje, 2015)
The article investigates attitudes towards English as a foreign language (EFL) by focusing on retrospective accounts of higher-education students' experience with learning English. The first part looks at individual factors affecting foreign language (FL) learning, such as attitudes towards FL learning and FL anxiety. The second part presents the results of a study conducted among students of the Faculty of Health Sciences at the University of Primorska. The main aim of the study was to identify students' attitudes towards their past EFL lessons and teachers and students' FL anxiety level. The results show that anxiety is a serious problem and that students exhibit alarmingly negative attitudes towards EFL lessons and teachers.
Keywords: learning anxiety; tesnobnost pri učenju; tuji jeziki; foreign language anxiety; angleščina; attitudes towards foreign language instruction; English; attitudes towards EFL teachers; learning; učenje; učenci; English language; tesnoba; osnovne šole; srednje šole